2012
DOI: 10.1093/bja/aer501
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebral oxygen saturation during thoracic surgery predicts early postoperative cognitive dysfunction

Abstract: Early cognitive dysfunction after thoracic surgery with SLV is positively related to intraoperative decline of S(ct)O(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 23 publications
3
70
1
1
Order By: Relevance
“…13 In addition, previous studies have shown that intraoperative regional cerebral desaturation is associated with lower postoperative MMSE scores in lung surgery patients. 12,28 Therefore, cerebral desaturation is considered a likely causative factor for POCD. A previous report 13 showed that cerebral desaturation was related to choice of anesthetic in OLV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In addition, previous studies have shown that intraoperative regional cerebral desaturation is associated with lower postoperative MMSE scores in lung surgery patients. 12,28 Therefore, cerebral desaturation is considered a likely causative factor for POCD. A previous report 13 showed that cerebral desaturation was related to choice of anesthetic in OLV.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] A previous study reported that cerebral oxygen saturation was higher in the sevoflurane anesthesia group than in the propofol anesthesia group during lung surgery. 13 Alternatively, a recent review found little evidence for differences in outcomes between inhalation and intravenous anesthesia during lung surgery.…”
Section: Résumémentioning
confidence: 98%
“…Several recent studies have suggested that poorer intraoperative hemodynamic function may be associated with adverse neurocognitive outcomes among patients undergoing surgical procedures requiring single-lung ventilation (10,11). Tang and colleagues (10) demonstrated that reduced cerebral oxygen saturation predicted early cognitive dysfunction as determined by using the Mini Mental State Examination in a sample of 76 surgical patients. Similarly, Suehiro and Okutai (11) found that longer duration of cerebral desaturation was associated with greater impairment in cognitive function following pulmonary lobectomy.…”
mentioning
confidence: 99%
“…The maintenance of slowed down saturation increases after 24 hours of treatment is associated with poorer prognosis [39]. Furthermore, tissue saturation in septic shock is found to increase significantly quicker in survivors compared to non-survivors [29,43].…”
Section: Use Of Oximetry For Evaluation Of Microcirculation and Oxygementioning
confidence: 99%
“…Tang and colleagues [29] have observed a relationship between low values of brain saturation and cognitive dysfunctions in the early postoperative period following the procedures with onelung ventilation. Moreover, patients with a decrease in brain saturation by at least 25% were hospitalized substantially longer [30].…”
Section: Use Of Brain Oximetry In Other Surgical Fieldsmentioning
confidence: 99%